2007
DOI: 10.1186/1476-072x-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Association of West Nile virus illness and urban landscapes in Chicago and Detroit

Abstract: Background: West Nile virus infection in humans in urban areas of the Midwestern United States has exhibited strong spatial clustering during epidemic years. We derived urban landscape classes from the physical and socio-economic factors hypothesized to be associated with West Nile Virus (WNV) transmission and compared those to human cases of illness in 2002 in Chicago and Detroit. The objectives were to improve understanding of human exposure to virus-infected mosquitoes in the urban context, and to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 37 publications
(34 reference statements)
4
129
4
1
Order By: Relevance
“…In Detroit and Chicago, Ruiz et al (2007) found WNV to be located in the inner suburbs with 1940-1960 era housing and moderate housing density. Although none of the associations were strong in the Northeast region, they were similar to the North Central region with positive associations with higher income developed areas and wetland areas and negatively associated with forested areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Detroit and Chicago, Ruiz et al (2007) found WNV to be located in the inner suburbs with 1940-1960 era housing and moderate housing density. Although none of the associations were strong in the Northeast region, they were similar to the North Central region with positive associations with higher income developed areas and wetland areas and negatively associated with forested areas.…”
Section: Discussionmentioning
confidence: 99%
“…3. These areas experienced high levels of WNV previously, especially in 2002 (Ruiz et al, 2007). The clusters evident in western Texas and northern California are in counties with fairly low populations that have had sporadic higher WNV rates (Sugumaran et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz and others showed that the highest WNV incidence rates in Chicago and Detroit occurred in inner suburbs with intermediate vegetation and population density. 38 Infection rates for WNV in wild birds were highest in urban/suburban areas in a study Georgia. 39 Brown and others investigated WNV disease incidence in the northeastern United States and found higher risk in the urban areas with intermediate forest cover.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation data were used to calculate slope using ArcGIS 9.3 (ESRI, Redland, CA). For further details see Ruiz et al (2007) and Loss et al (2009a). Of the eight sites, five can be considered residential areas (S1, S5, S7, S10, S11) and three were ''natural areas'' (WW, SC, EC).…”
Section: Datamentioning
confidence: 99%